Inter-Rater Reliability of Preprocessing EEG Data: Impact of Subjective Artifact Removal on Associative Memory Task ERP Results - Shirk, Steven D.; McLaren, Donald G.; Bloomfield, Jessica S.; Powers, Alex; Duffy, Alec; Mitchell, Meghan B.; Ezzati, Ali; Ally, Brandon A.; Atri, Alireza (Frontiers in Neuroscience, 2017)
The processing of EEG data routinely involves subjective removal of artifacts during a preprocessing stage. Preprocessing inter-rater reliability (IRR) and how differences in preprocessing may affect outcomes of primary event-related potential (ERP) analyses has not been previously assessed. Three raters independently preprocessed EEG data of 16 cognitively healthy adult participants (ages 18-39 years) who performed a memory task. Using intraclass correlations (ICCs), IRR was assessed for Early-frontal, Late-frontal and Parietal Old/new memory effects contrasts across 8 regions of interest (ROIs). IRR was good to excellent for all ROIs; 22 of 26 ICCs were above 0.80. Raters were highly consistent in preprocessing across ROIs, although the frontal pole ROI (ICC range 0.60-0.90) showed less consistency. Old/new parietal effects had highest ICCs with the lowest variability. Rater preprocessing differences did not alter primary ERP results. IRR for EEG preprocessing was good to excellent, and subjective rater-removal of EEG artifacts did not alter primary memory-task ERP results. Findings provide preliminary support for robustness of cognitive/memory task-related ERP results against significant inter-rater preprocessing variability and suggest reliability of EEG to assess cognitive-neurophysiological processes multiple preprocessors are involved.